Genetic Signatures of Centenarians: Implications for Achieving Successful Aging - Caruso, Calogero; Aiello, Anna; Accardi, Giulia; Ciaglia, Elena; Cattaneo, Monica; Puca, Annibale (Current Pharmaceutical Design, 2019)
The extraordinary rise in the old population in the Western world underscores the importance of studies on aging and longevity to decrease the medical, economic and social problems associated with the increased number of non-autonomous individuals affected by invalidating pathologies. Centenarians have reached the extreme limits of the human life span. They are the best example of extreme longevity, representing selected individuals in which the appearance of major age-related diseases has been consistently delayed or avoided. There is growing evidence that the genetic component of longevity becomes higher with survival at the age of over 90 years. For centenaries, it reaches up to 33% for women and 48% for men. Therefore, exceptional longevity is a complex, hereditable trait that runs across generations. Longevity should correlate either with the presence of protective alleles or the absence of detrimental alleles. The aim of this review is to discuss the possible attainment of successful aging in the context of the lessons learned from centenarian genetics.
Keywords: successful aging